The Application of AI Technology in Vocational High School Curriculum Design Based on Individual Student Skills in Facing the Challenges of the 21st Century Industry - Liza Efriyanti; Firdaus Annas (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2025)
Vocational high schools (SMK) are confronted with the challenge of adapting their curricula to align with the demands of industrial development in the 21st century. An inappropriate curriculum may result in students being inadequately prepared to navigate the demands of the professional world. Consequently, the objective of this research is to optimize the SMK curriculum through the utilization of an AI-based system, thereby enabling students the curriculum to be tailored to the specific skill requirements of individual. The methodology employed is Design-Based Research (DBR), which entails the analysis of student skill data, the design of an adaptive curriculum, and the evaluation of said curriculum through trials. The research comprised several phases, beginning with data collection and student skills analysis and concluding with an evaluation of student satisfaction with the implemented curriculum. The findings indicated that the introduction of an AI-assisted personalized curriculum resulted in an average improvement of 15% in students' practical skills over a six-month period. Furthermore, student satisfaction with the implemented curriculum increased by 25%, from 70% at the outset of implementation to 95% following the introduction of the AI-based system. This research can serve as a reference point for the development of more adaptive and responsive SMK curricula.